Linking Favoritism and Work Pressure to Turnover Intention: The Mediating Role of Job Satisfaction in the Outsourcing Industry - Randi Dwi Shaputra; Praningrum Praningrum (Journal of Enterprise and Development)
Purpose: This study aims to analyze the impact of favoritism and work pressure on turnover intention, with job satisfaction as a mediating variable in the outsourcing industry. Method: This research employs a quantitative approach, using data collected through both offline and online questionnaires distributed to 119 outsourcing employees at PT Kinarya Selaras Solusi. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. Result: The findings indicate that favoritism and work pressure have a significant positive effect on employee turnover intention, while job satisfaction has a significant negative effect. Additionally, favoritism and work pressure significantly and negatively affect job satisfaction. Job satisfaction serves as a mediating variable by reducing the impact of favoritism and work pressure on turnover intention. Practical Implications for Economic Growth and Development: These findings offer insights for outsourcing companies seeking to reduce employee turnover. By addressing issues related to favoritism and work pressure, companies can enhance job satisfaction and lower turnover rates, thereby contributing to economic growth through increased workforce stability and efficiency in Indonesia’s outsourcing sector. Originality/Value: This study provides original value by integrating favoritism, work pressure, job satisfaction, and turnover intention into a single research model within the context of Indonesia’s outsourcing industry—an area that has received limited academic attention despite its high employee turnover rates.